2020
DOI: 10.3390/cryst10040262
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the Segregation of Germanium in Silver Nanolayers

Abstract: It is generally acknowledged that using germanium as a wetting film for silver nanolayers decreases the surface roughness of the metal. However, germanium atoms also tend to segregate towards the surface of silver films, increasing ohmic losses in the structure. Here we propose an Au/Ge/Ag based structure where the segregation of germanium in silver is inhibited. X-ray photoelectron spectroscopy (XPS) results show that for the Au/Ge/Ag system, the surface concentration of germanium drops by an order of magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Moreover, the excess Zn atoms present in the interstitial sites on the surface and at the grain boundaries induce strain in a lower volume of the crystal lattice than the excess Zn atoms present in the interstitial lattice sites inside the ZnO grains [44,45]. Although elastic strain energy can properly be calculated only for mixtures of monoatomic substances, its contribution to the enthalpy of segregation is always negative [26], indicating that the segregation of the excess Zn atoms towards the surface or the grain boundaries of the ZnO films might be spontaneous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the excess Zn atoms present in the interstitial sites on the surface and at the grain boundaries induce strain in a lower volume of the crystal lattice than the excess Zn atoms present in the interstitial lattice sites inside the ZnO grains [44,45]. Although elastic strain energy can properly be calculated only for mixtures of monoatomic substances, its contribution to the enthalpy of segregation is always negative [26], indicating that the segregation of the excess Zn atoms towards the surface or the grain boundaries of the ZnO films might be spontaneous.…”
Section: Discussionmentioning
confidence: 99%
“…Electron beam physical vapour deposition (e-beam PVD) technique is commonly used to produce both metallic [24][25][26] and oxide coatings [27] including zinc oxide films [16,19]. The influence of microstructure on the optical response of zinc oxide films fabricated under various conditions, such as the substrate temperature (and/or annealing after deposition) as well as deposition rate, has been investigated in recent years [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The different growing conditions of TiO 2 leads to varying properties of these coatings and thus to various applications. In this research, the titanium dioxide films were fabricated by the electron beam physical vapor deposition (e-BEAM PVD) technique, which is a time- and cost-effective method commonly used to produce both metallic [ 35 , 36 , 37 ] and oxide coatings [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of germanium wetting layer in Au(Ag)/Ge/Au(Ag) multilayer systems has been studied by A.Ciesielski at al. [5]. It was found that, in the Au/Ge/Ag structure, the segregation of germanium in silver is inhibited; however, is not completely canceled.…”
mentioning
confidence: 99%